Umowy o korzystanie z cudzych rozwiązań technicznych w obrocie pomiędzy krajami RWPG (w świetle praktyki przedsiębiorstw polskich w latach 1981-1987) - Nowicka, Aurelia (Wydział Prawa i Administracji UAM, 1989)
The article is based on empirical research conducted by the author in the Ministry of Foreign Economic Relations. The research comprised licence agreements (for both export and import), concluded between 1981 -1987 by Polish enterprises with partners from the CMEA countries. Analysing the contents of the contracts the author takes into account the stipulations of the CMEA documents which in the form of "directives" regulate the circulation of so-called „.scientific and technical works". Taken into account were the stipulations of Organizational, Methodical, Economic and Legal Foundations for Scientific and Technological Co-operation of the CMEA Member States of 1972 (in the 1986 version) and the provisions of „model forms of licencing agreements" issued by the CMEA Secretariat in 1975. The purpose of the analysis was to establish to what degree the solutions recommended for application within the CMEA influence the praxis of shaping the contents of contracts. It should be emphasized that licence relations have not yet been regulated in the acts of the so-called „CMEA common '' law". Besides, the author analyses the contents of particular clauses, especially those of importation contracts, from the viewpoint of their agreement with Polish norms regulating the transfer of technology contained in the 1986 Regulation on Principles and Procedure of Exportation and Importation of Scientific and Technical Achievements issued by the Minister of Foreign Trade. The author aims at establishing to what degree Polish licencees are able to secure for themselves preferred elements of the contents of contracts and to what degree contracts for importation of technology from the CMEA countries are tainted with restrictive practices. The author carries out a survey of typical licence clauses, in particular clauses regulating the extent and character of a licence, the transfer of technical documentation, the exchange of technological improvements, the licensor's legal and technical protective measures and the liability for infringing them, technical assistance, licence fees and their payments, measures to protect the secrecy of know- -how, the clauses regulating the settling of disputes and the choice of applicable law. Then, the author turns her attention to the areas of inadequate contractual regulation (especially the problems of liability and the choice of applicable law). She also discovers in importation contracts. concluded with the CMEA countries the existence of practices restricting the economic activity of Polish licences. From among the restrictive clauses indicated in the Regulation of 1986 the author finds the restrictions as to the right of granting sublicences, exportation restrictions and interdictions to question the licensor's protective title. In that connection the author deals with the character of Polish legal norms regulating the transfer of technology and analyses the relation of these provisions to the norms of the Law on Counteracting Monopolistic Practices. She concludes that restrictive licence clauses may be subject to, sanctions provided for in the Law. The last part of her article is devoted to the problem of transfer of technology within joint ventures carried out with partners from the CMEA countries. Legal foundations of such a form of co-operation and means of transfering the technology within joint ventures have been discussed.
Contracts for use of foreign technical works in relation between the CMEA countries (in the light of praxis of Polish enterprises in years 1981-1987)